The Bhagavad Gītā: A Combative Text - Khatri, Tilak Bahadur (NUTA Journal, 2022)
This research article deals with the action-oriented (karmayogic) commentaries of the Bhagavad Gītā given by some of the major commentators in nineteenth-century India. The study is relevant to understanding the text's karmayogic dimension and practical value. The article addresses the research problems concerning the karmayogic interpretations of the text and their pragmatic value in social transformation. Does the scripture teach humanity the value of action/karma in this cosmic world? Do the karmayogic teachings of the scripture have pragmatic value to bring specific social change? The article seeks answers to the aforementioned research questions through the review-based analysis of the text's karmayogic commentaries of some of the well-known nineteenth-century Indian commentators. The study has included the commentaries of Bankim, Vivekananda, Tilak, Gandhi, Aurobindo, and Vinoba. The study reveals that the above commentators of the Gītā discover the seeds of karma-yoga in the text and the majority of the commentators see the text's pragmatic value in bringing social change. Most of the above nineteenth-century Indian commentators view the scripture as a combative text and employ it as a potent weapon in the struggle against British colonialism.